CGE Analysis of the Impact of the 2024 Minimum Wage Increase on the National Economy in Indonesia - Annazah, Nur Siti; Hazami, Muhammad Fikrie; Nasution, Faizal Amir P; Tobing, Henriko (Jurnal Ketenagakerjaan, 2024)
One of the minimum wage problems is caused by workers/laborers' needing to agree with the wage increase set. The minimum wage increase is still minimal compared to the high worker need. The Labor Organization president called the government to raise the provincial minimum wage (UMP) and district/city minimum wage (UMK) 2024 by 15%. This figure is obtained from the Decent Living Needs (KHL) survey results and other indicators such as inflation and economic growth. On the other hand, the minimum wage increase of 15% is considered by employers to be unrealistic, considering the condition of the national economy is hit by uncertainty. The government said that determining the minimum wage based on PP 36/2021 and considering the welfare of workers/laborers’ also looks at the Company's capabilities. This paper aims to see new macroeconomic and welfare conditions due to the increase in the minimum wage by 15%. Using the general equilibrium model of static computing (CGE), the analysis results show that an increase in the minimum wage leads to a decrease in demand for labor, especially in labor-intensive sectors. The increase in wages impacts increasing household income, thus indicating an increase in household welfare. However, inflationary pressures brought about by the minimum wage increase mask the increase in revenue, resulting in a decrease in household consumption budgets. This translates into a loss of net well-being, with a more significant impact on urban households than rural households. The output of most sectors, especially labor-intensive sectors, declined, but nominal GDP increased. The increase in nominal GDP is due to rising prices, not actual economic output.